2017
DOI: 10.18632/oncotarget.22547
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-196a2 rs11614913 and miR-499 rs3746444 polymorphisms with cancer risk: a meta-analysis

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNA molecules, which participate in diverse biological processes and may regulate tumor suppressor genes or oncogenes. Rs11614913 in miR-196a2 and rs3746444 in miR-499 are shown to associate with increased/decreased cancer risk. This meta-analysis was performed to systematically assess the overall association.Materials and MethodsWe searched Pubmed, Web of Knowledge, EMBASE, Chinese National Knowledge Infrastructure (CNKI) databases until December 2016 to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 84 publications
1
24
0
Order By: Relevance
“…All four miRNA gene variant associations noteworthy to detect an OR of 1.1 that were also noteworthy (FPRP < 0.2) were included in these 16 comparisons. The other 12 comparisons were miR‐196a2/rs11614913 T vs. C (OR, 1.21; P < .0001); miR‐27a/rs895819 GG vs. AA + AG (OR, 1.49, P < .001) and colorectal cancer ; miR‐196a2/rs11614913 C vs. T (OR, 1.40, P < .00001) and oesophageal cancer ; miR‐146a/rs2910164 G vs. C (OR, 1.15, P < .001); miR‐196a2/rs11614913 T vs. C (OR, 0.77, P < .00001) and gastric cancer ; miR‐146a/rs2910164 C vs. G (OR, 1.19, P < .001) and bladder cancer ; miR‐499/rs3746444 homozygous model (OR, 1.64, P < .001) and breast cancer ; miR‐146a/rs2910164 CC vs. GG + GC (OR, 0.52, P < .001); miR‐499/rs3746444 (OR, 2.07, P < .001) and cervical cancer ; miR‐499/rs3746444 GA vs. AA (OR, 1.60, P < .001) and prostate cancer ; miR‐146a/rs2910164 CC vs. GG (OR, 1.28, P < .001) and lung cancer ; and miR‐499/rs3746444 G vs. A (OR, 1.57, P < .001) and oral squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…All four miRNA gene variant associations noteworthy to detect an OR of 1.1 that were also noteworthy (FPRP < 0.2) were included in these 16 comparisons. The other 12 comparisons were miR‐196a2/rs11614913 T vs. C (OR, 1.21; P < .0001); miR‐27a/rs895819 GG vs. AA + AG (OR, 1.49, P < .001) and colorectal cancer ; miR‐196a2/rs11614913 C vs. T (OR, 1.40, P < .00001) and oesophageal cancer ; miR‐146a/rs2910164 G vs. C (OR, 1.15, P < .001); miR‐196a2/rs11614913 T vs. C (OR, 0.77, P < .00001) and gastric cancer ; miR‐146a/rs2910164 C vs. G (OR, 1.19, P < .001) and bladder cancer ; miR‐499/rs3746444 homozygous model (OR, 1.64, P < .001) and breast cancer ; miR‐146a/rs2910164 CC vs. GG + GC (OR, 0.52, P < .001); miR‐499/rs3746444 (OR, 2.07, P < .001) and cervical cancer ; miR‐499/rs3746444 GA vs. AA (OR, 1.60, P < .001) and prostate cancer ; miR‐146a/rs2910164 CC vs. GG (OR, 1.28, P < .001) and lung cancer ; and miR‐499/rs3746444 G vs. A (OR, 1.57, P < .001) and oral squamous cell cancer …”
Section: Resultsmentioning
confidence: 99%
“…Wang et al showed increase of the cancer risk in homozygote comparison model due to miR - 196a2 rs11614913 CC genotype as compared to TT genotype [ 19 ]. In a meta-analysis, authors concluded that there was significant linkage between the miR - 196a2 rs11614913 and a reduced risk of cancer, especially a lower risk of gastric cancer and colorectal cancer or for Asian subgroup of population [ 20 ]. Furthermore, in the meta-analysis, Xu et al reported the most probable contribution of the rs11614913 reduces cancer susceptibility, particularly breast cancer in Asia [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-499 rs3746444 has been proved to be signi cantly associated with increased risk of cancer of the respiratory system, digestive system,urinary system and gynecological system [42][43][44][45][46][47][48][49][50][51][52][53].Existing studies have been veri ed that the MiRNA-499(rs3746444 T > C) gene polymorphism can control the expression level of SOX gene. Due to the up-regulation of SOX6 gene, the anti-apoptosis function of MiRNA-499(rs3746444 T > C) can be reversed [54].…”
Section: Discussionmentioning
confidence: 99%